Wealth concentration: an item imputation of poverty and analogous study on social business hybrid modeling and contingent method of using geometrical analysis in social business - Nur, Tahmid Tawsif (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.